2015
DOI: 10.4103/2229-5070.149919
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of Blastocystis spp. in diarrheic patients

Abstract: Background:Many laboratories currently diagnose Blastocystis spp. infections by looking for the presence of vacuolar forms in faeces and the amoeboid form in diarrheal stools.Objectives:To investigate the best direct method in diagnosis of Blastocystis spp. and to study different morphological forms of the parasite.Materials and Methods:The study was carried out on one thousand and two hundred diarrheic stool samples. All samples were examined using direct smear, iodine stained smear, formalin-ether concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
3
25
0
7
Order By: Relevance
“…However, the pathophysiology of Blastocystis infections in Korea remains undefined, and highly sensitive quantitative tools would increase our understanding of Blastocystis infections. Elghareeb et al found a wide range in diagnostic sensitivity between different Blastocystis detection methods [22]. Xenic in vitro cultures (XIVC) of Blastocystis exhibited a heightened positivity of 22.8%, compared to 12.3% with trichrome staining, 10.0% with formalin-ether concentration, 6.0% with an iodine-stained smear, and 3.5% with a direct smear [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathophysiology of Blastocystis infections in Korea remains undefined, and highly sensitive quantitative tools would increase our understanding of Blastocystis infections. Elghareeb et al found a wide range in diagnostic sensitivity between different Blastocystis detection methods [22]. Xenic in vitro cultures (XIVC) of Blastocystis exhibited a heightened positivity of 22.8%, compared to 12.3% with trichrome staining, 10.0% with formalin-ether concentration, 6.0% with an iodine-stained smear, and 3.5% with a direct smear [22].…”
Section: Discussionmentioning
confidence: 99%
“…Elghareeb et al found a wide range in diagnostic sensitivity between different Blastocystis detection methods [22]. Xenic in vitro cultures (XIVC) of Blastocystis exhibited a heightened positivity of 22.8%, compared to 12.3% with trichrome staining, 10.0% with formalin-ether concentration, 6.0% with an iodine-stained smear, and 3.5% with a direct smear [22]. Several PCR assays targeting the SSU rRNA gene have been previously developed for detection and discrimination among Blastocystis isolates directly in stool samples, and these assays have been more sensitive than XIVC [23].…”
Section: Discussionmentioning
confidence: 99%
“…infection was noted to be 24 (10.5%), 24 (10.5%), and 64 (27.8%), by direct microscopy, trichrome method, and PCR, respectively. Generally, stained and direct smear methods have lower sensitivity, 32,33 while PCR was found to be the most effective diagnostic approach. 25,34 Owing to the difficulty in collecting three consecutive stool samples, we obtained one specimen from each participant.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocystis spp. prevelansı gelişmiş ülkelerde %1,5-10, gelişmekte olan ülkelerde %30-60 arasında değişmektedir [1][2][3] . Zorunlu anaerop olup nötral pH'da 37ºC'de üremektedir 4 .…”
Section: Introductionunclassified
“…Zorunlu anaerop olup nötral pH'da 37ºC'de üremektedir 4 . Bilinen formları vakuolar, granular, multivakuolar, ameboid ve kistik formlardır 3 .…”
Section: Introductionunclassified